An overview of oilseeds and oil scenario, seed chain and strategy to energize seed production - CHAUHAN, J S; CHOUDHURY, P R; PAL, S; SINGH, K H (The Indian Journal of Agricultural Sciences, 2021)
Oilseeds in India accounted for 15.7% of the total arable land during 2017-18. The present paper discusses oilseeds and vegetable oil scenario in India; seed chain, current status of quality seed and strategies for seed production & development to enhance oilseeds output through bridging the vast untapped potential of the available technologies to reduce heavy dependence on oil imports. Of the nine annual oilseeds, groundnut, soybean, rapeseed-mustard and sesame during the last seven years (2012-13 to 2018-19) contributed 89.2-94.4% to acreage and 90.4%-95.0% to production of oilseeds. The area, production and yield of oilseeds attained an overall increase of 131.1%, 510.9% and 164.2%, respectively, from 1950-51 to 2018-19. Of the several programmes initiated to harness the vast exploitable yield reservoir of oilseeds, National Mission on Agricultural Extension and Technology launched during XII plan and Mega seed project during 2005-06, had great impact on enhanced availability of quality seed of newly released varieties and thus production of oilseeds. Considering annual growth of demand for edible oil, population growth and the per capita consumption of about 102.3 m t of oilseeds would be required by 2030. To meet this formidable challenge, the assets such as vibrant crop specific improvement programmes, 187 newly released high yielding varieties, improved crop management technologies, robust and effective seed chain and climate favouring seed production of diverse oilseeds are available in the country.